Exceptions to the rule not to allocate public revenue - عبدالقادر, بان صلاح; نعمة, رغد عبدالله (Journal of Legal Sciences, 2021)
The general  budget  is  the  state’s  annual financial program that manages public facilities   and   services   in  it، which  contains  public  earning  and  expenses. The general budget is   subject to several principles.  The most   important of these principles is the principle of generality، watch includes the proper management of the financial program through two basic principles the principle of allocating public expenditures and the principle of not allocating revenues.